Framing healthcare instruction an information literacy handbook for the health sciences - Young, Lauren M., 1979-; Hinton, Elizabeth G., 1981- (Medical Library Association books., 2019)
"Framing Healthcare instruction: An Information Literacy Handbook for the Health Sciences is a step-by-step guide to integrating the ACRL Framework for Information Literacy into health sciences librarianship. Although this topic has been touched on briefly in previous publications, this book is dedicated exclusively to the unique considerations of the health sciences. With over fifty case studies describing explicit lesson plans and assessments, health sciences librarians who may be new to the Framework or are looking for ready-made lesson plans will find this guide easy to navigate and to apply to their own educational sessions. Multiple disciplines are covered, including: nursing, medicine, allied health, veterinary medicine, and more. In addition to the practical application of the case studies, the books covers in depth each part of the Framework and how it relates to students in the health science.--Description, EBSCOhost.